Theoretical study on the solvent‐free self‐catalyzed coupling mechanism of a chiral vicinal diamine and isobutyraldehyde mediated by the outgrowth H2O. Issue 11 (14th March 2023) - Cheng, Xueli; Zhao, Yanyun; Liu, Jingjing; Sun, Junshan; Miao, Yanfei; Ling, Baoping
Abstract: The self‐catalyzed addition of a chiral vicinal diamine with two isobutyraldehyde molecules and the subsequent diaza‐Cope rearrangement between two diimines were investigated systematically by M06‐2X method in conjunction with the 6‐311+G(d) basis set. Our theoretical model shows that, 1) the solvent‐free coupling of the vicinal diamine and isobutyraldehyde molecules produces a relative stable compounds with an imidazolidine‐dihydro‐1, 3‐oxazine fused ring instead of imine intermediates; 2) the assistance of a yielded water molecule can significantly decrease the free‐energy barriers of the ring‐recombination and ring‐opening processes by borrowing a hydrogen atom from it; 3) the two addition processes with the free‐energy barriers of 150.0 and 159.0 kJ/mol, respectively, and the successive formation of the five‐membered ring with a barrier of 164.1 kJ/mol control the whole reaction system. Abstract : The intriguing solvent‐free and self‐catalyzed coupling of ( R, R )‐1, 2‐bis(2‐hydroxyphenyl)‐1, 2‐diaminoethane with two isobutyraldehyde molecules to yield chiral diimines were studied in detail at M06‐2X/6‐311+G(d) level. The two chiral centers in the mother diamine are fixed in this work.